Fiscal Mechanism of Dhangadhi Sub-Metropolitan City: Revinue Generation and Expenditure Allocation (AMC Journal (Dhangadhi), 2025)
This study explores the connection between revenue sources and expenditures in achieving the goals outlined in the development plan. It examines the revenue and expenditure patterns of Dhangadhi Sub-metropolitan City over a five-year span (2076–2080). The study first assesses the structural trends in revenue generation and spending. Then, it evaluates the effectiveness of current revenue sources and suggests additional avenues for revenue enhancement. Finally, it establishes a link between revenue streams and expenditures. A combination of descriptive and analytical research methods was employed. To examine revenue and expenditure trends, descriptive statistical tools were utilized. Additionally, insights were gathered through panel discussions and key informant interviews. The interviewees were selected from various sectors, including poultry farming, healthcare, trade, education, hardware supply, hospitality, and public transport. Findings indicate that the service sector consistently drives more than two-thirds of the local economy, while manufacturing has remained relatively weak, contributing less than 10 percent. Expanding the tax base could significantly enhance revenue collection. Currently, the city follows a centralized approach—pooling all revenue into a single fund before allocating expenditures. However, discussions suggest that a more structured approach, with designated revenue and expenditure portfolios, might be beneficial. These insights could serve as a valuable resource for both policymakers and taxpayers in Dhangadhi Sub-metropolitan City.